DINAMIKA POPULASI IKAN TONGKOL ABU-ABU (Thunnus tonggol) YANG DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA PEMANGKAT - Syajidah, Hanna; Sirodjul Munir, Achmad Mulyadi; Hadinata, Fitra Wira (Fakultas Pertanian Universitas Tanjungpura, 2024)
Longtail tuna (Thunnus tonggol) is one of the types of catches landed at the Pemangkat Nusantara Fishing Port. This study aims to determine the frequency distribution of fish length, length and weight relationships, growth parameters, as well as mortality and exploitation rates. Analysis of population parameters using Stock Assessment Tools FISAT II software Ver. 1.2.2. This research was conducted from March to June 2023. The method used in sampling longtail tuna is systematic random sampling method. The results of the study of the population parameters of longtail tuna landed at PPN Pemangkat showed the frequency distribution of the length of the cagak obtained a minimum length of 37 cm and a maximum length of 72 cm. The equation of the relationship between length and weight of tuna is W = 0.0104x3.1258 with a coefficient of determination (R2) of 0.876. The growth pattern is positive allometric. The growth coefficient (K) was 0.40 per year with an asymptotic length (Lâˆž) of 79.65 and an initial theoretical age (t0) of 225 per year. The total mortality rate (Z) was 1.05 per year, natural mortality (M) was 0.76 per year, capture mortality rate (F) was 0.29 per year and exploitation rate (E) was 0.28. This exploitation rate value has not exceeded the optimum exploitation value of 0.5.